Isolation and Thermal Stabilization of Bacteriocin Nisin Derived from Whey for Antimicrobial Modifications of Polymers - Pavlina Holcapkova; Zuzana Kolarova Raskova; Martina Hrabalikova; Alexandra Salakova; Jan Drbohlav; Vladimir Sedlarik (International Journal of Polymer Science)
This work describes novel alternative for extraction of bacteriocin nisin from a whey fermentation media and its stabilization by using polyethylene glycol as matrix with high practical applicability. This product was compared with commercially available nisin product stabilized by sodium chloride and nisin extracted and stabilized by using ammonium sulfate and polysorbate 80. The stability of samples was tested by means of long-term storage at −18, 4, 25, and 55°C up to 165 days. The nisin content in the samples was determined by high-performance liquid chromatography and electrophoresis. In addition, effect of whey fortification with lactose on nisin production and antibacterial activity studied against Staphylococcus aureus was tested. Results show that stabilization by polyethylene glycol provides enhanced nisin activity at 55°C after 14 days and long-term stability at 25°C with keeping antibacterial activity.